1993
DOI: 10.1115/1.2906707
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Inlet Swirl on the Rotordynamic Shroud Forces in a Centrifugal Pump

Abstract: The role played by fluid forces in determining the rotordynamic stability of a centrifugal pump is gaining increasing attention . The present research investigates the contributions to the rotordynamic forces from the discharge-to-suction leakage flows between the front shroud of the rotating impeller and the stationary pump casing. In particular, the dependency of the rotordynamic characteristics of leakage flows on the swirl at the inlet to the leakage path was examined . An inlet guide vane was designed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 5 publications
0
14
0
1
Order By: Relevance
“…6. It is noteworthy that the effect of the leakage flow on the fluid force moment on the precessing back-shroud is the same as that of the inlet swirl on the fluid force on the whirling shroud (Childs [1989] and Guinzburg et al [1993]).…”
Section: Measurements Of the Flow Inmentioning
confidence: 94%
See 1 more Smart Citation
“…6. It is noteworthy that the effect of the leakage flow on the fluid force moment on the precessing back-shroud is the same as that of the inlet swirl on the fluid force on the whirling shroud (Childs [1989] and Guinzburg et al [1993]).…”
Section: Measurements Of the Flow Inmentioning
confidence: 94%
“…Moreover, rotordynamic fluid forces on an impeller shroud with a small shroud/casing clearance are destabilizing (Ohashi et al [1988] and Adkin et al I1988]). For the shroud forces of a whirling centrifugal impeller, numerical (Childs [1989] and Baskharone et al [1994]) and experimental (Guinzburg et al [1993]) investiga-tions have been carried out to see the effect of leakage flow in the shroud/casing clearance and inlet swirl at the entrance of the clearance. It was found that the fluid forces on the shroud become more rotordynamically destabilizing with increasing the inlet swirl at the impeller outer radius.…”
Section: Introductionmentioning
confidence: 99%
“…Though some early data on the rotordynamic forces in a centrifugal pump were obtained by Shoji and Ohashi [8], the Caltech program added greatly to the data base. Data were obtained for many different types of impellers (centrifugal and axial, shrouded and unshrouded, with and without cavitation), for many different types of volutes and for parametric variations of the forces with pump operating point, pump cavitation and various clearances and other factors [6,7,[9][10][11][12][13][14][15][16][17][18][19]. Typical data for the dimensionless normal and tangential forces, F n and F t ; as a function of the frequency ratio, o=O; are presented in Figure 3 for a conventional centrifugal pump impeller operating in a single vaneless volute.…”
Section: Measurements In Centrifugal Pumpsmentioning
confidence: 99%
“…Guinzburg et al [13,14,29], Uy and Brennen [16,17] and Hsu and Brennen [18] also conducted experimental investigations of the effect on the rotordynamic forces of the inlet swirl to the leakage flow path. This was accomplished by installing guide vanes at the leakage inlet to introduce pre-rotation in the direction of shaft rotation.…”
Section: Effects Of Inlet Swirlmentioning
confidence: 99%
See 1 more Smart Citation